Model Predictive Control Design of Pressure Swing Distillation for Methanol-C5 Separation - Rilam Alfa Firdaus, Abdul Wahid (International Journal of Advanced Science and Technology, 2020)
The azeotropic mixture that is greatly influenced by pressure is usually separated bypressure-swing distillation (PSD). This paper investigates the control selection of thePSD system. The PSD scheme was developed by Luyben. Model predictive control (MPC)is used as an alternative control method because it had a better response compared to theproportional-integral (PI) controller. MPC utilizes a dynamic model to make a controlaction toward the process. Generating the model is a crucial step for the MPC to workaccurately. In this work, the model representing the process was approached by the firstorder plus dead time (FOPDT) model. The steady-state and dynamic simulations werecarried out with HYSYS V11. The fine-tuning method was used to find the optimum tuningparameter of MPC meanwhile, the PI controller was tuned by auto-tuner. The resultsshow that MPC was successfully implemented to the process and the control performancehas increased by 21-52% in the set-point tracking test and 5-42% in disturbance rejectiontest compared to the PI controller.